ANALISIS PRODUKTIVITAS DENGAN METODE MULTI FACTOR PRODUCTIVITY MEASUREMENT MODEL - Yolandha Angelica Agry Culturianingtyas; Panji Deoranto; Dhita Morita Ikasari (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2014)
Abstrak Tujuan dari penelitian ini adalah untuk mengetahui tingkat produktivitas perusahaan dan usulan untuk meningkatkan produktivitasnya di masa mendatang menggunakan Metode Multi Factor Productivity Measurement Model. Dari hasil penelitian, tingkat produktivitas PT Inti Luhur Fuja Abadi sebesar 81.43% pada periode yang diukur (periode 2). Tingkat produktivitas ini mengalami penurunan produktivitas sebesar 18.57% dari periode dasar (periode 1). Hal ini menyebabkan perusahaan kehilangan peluang mendapatkan keuntungan sebesar Rp 136,293,924. Rencana usulan peningkatan produktivitas untuk PT Inti Luhur Fuja Abadi difokuskan pada input bahan baku terutama Kakap Merah dengan membuat perencanaan kuantitas bahan baku yang akan digunakan serta biaya pembelian bahan baku tersebut dengan permintaan dari konsumen agar lebih efisien dalam menghasilkan output.Kata Kunci :MFPMM, Pengukuran Produktivitas, Tingkat Produktivitas Abstract PT Inti Luhur Fuja Abadi is one of the companies in industrial freezing of fish and exported to several countries and have mission to consistently provide quality products and the best services to customers. However, it remains unknown how the conditions and the level of achievement of the company's performance over the years because this company has not yet done about productivity measurement. The aim of this study was to determine the level of productivity of the company and the proposal to increase the productivity in the future using MultiFactor ProductivityMeasurementModel method. The results showed that the level ofproductivityofPTInti Luhur Fuja Abadiof81.43% in the measured period (period 2). The level of productivity decreasedby18.57% from the base period(period 1). It caused the company lose an opportunity to get a profit ofRp136,293,924. Productivity improvements in the proposed plan ofPTInti Luhur Fuja Abadifocused on the input of raw materials, especially Red Snapper with a plan that adjusts the quantity of raw materials to be used and the cost of purchasing the raw materials to the demand of consumers to be more efficient in generating output.Keywords: Level of productivity, Multi Factor Productivity Measurement Model, Productivity Measurement